Les risques en milieu urbain : éléments de réflexion - Pascale Metzger; Robert D'Ercole (EchoGéo)
This text is a contribution to the debate on the question of the risks in urban zones. It exposes the various approaches of this question, and focuses on the conceptual problems put by the definition of the risks by the social sciences, in particular by the geography. The text exposes the multiple points of view and dimensions of the risk. It discusses the different notions which enter in its definition, and argues about the necessity of taking into account " what we can lose " in the definition of the risk. That position sends back on one hand to the social construction of the risk, on the other hand to the choice between the risks operated by the public policies. The text insists on the necessity for the social sciences and the geography to build a concept cleared of the superiority of the hazard.